Strategic motivators for integrating energy economics into the developing garments sector: A comprehensive analysis from Bangladesh - Amam Hossain Bagdadee; Sakib Hossain; Li Zhang (Heliyon)
This research explores the strategic incentives driving the integration of energy economics into Bangladesh's evolving garment sector. The garments industry is a significant revenue generator for the nation; it is currently entering its prime phase, where the balance between economic growth and sustainability becomes critical. This paper presents a landscape by evaluating trends, framework conditions, and scenario-based case studies. These may lead to perceptions regarding integrating energy economic trends and their impact on the sector's efficiency, competitiveness, and sustainability levels. This case study proposes exclusive strategies to promote energy-efficient garment manufacturing in Bangladesh. This paper provides practical tools for Bangladesh policymakers, investors, and garment manufacturers to highlight the economic benefits of adopting energy-efficient practices. It notifies about policies, contributes to better decision-making, and fuels sustainability investments. It also calibrates the sector with global sustainability standards that promote long-term competitiveness, environmental responsibility, and resilience in the garments industry.